"INFLUENCE OF BIOCARBON MADE WITH SOLID ORGANIC WASTE ON THE QUALITY AND PRODUCTION OF POTATO CROPS AT THE EXPERIMENTAL ECOLOGICAL CENTER OF TUYU RURI" (Aporte Santiaguino, 2022)
The farmers in the town of Tuyu Ruri Bajo in Marcará have used too many agrochemicals over time to improve the quality and production of their potato crops. Leading to the contamination of different natural resources and generating long-term damage to people's health.The objective of the research was to determine the influence of an organic product called "biochar", which was produced through a process of pyrolysis of organic solid waste, in the quality and production of the agricultural crop of the potato in the Ecological Experimental Center of Tuyu Ruri.A randomized complete block design with four blocks and four treatments with biochar percentages of 0%, 5%, 10% and 15% was carried out; evaluating different morphometric and biological indicators.The results related to the monitoring of the treated agricultural crop showed significant improvements in height, the phytosanitary status of the crop, as well as in the quantity and weight of the potatoes obtained.It was concluded that the biochar produced by pyrolysis of organic solid waste influenced the improvement of the quality and production of the potato crop in the Ecological Experimental Center of Tuyu Ruri.